(untitled) (ELang | An English Language Education Journal, 2021)
The research paper entitled “The Effectiveness Of Using Cartoon Videos In Improving Students’ Listening Skill”. The aim of the research paper is to find out whether or not the use of cartoon video is effective to improve listening skill and also to know students’ responses towards the use of cartoon video at the third grade of SMP Yadika 2 Paseh in academic 2021/2022. The research method is a pre- experimental using 25 students as sample from 75 students of population. To obtain the data the researcher uses pre-test, post-test and questionnaire. The sample is given the pre-test before the treatment and post-test afterwards. The post-test and the questionnaire are given in order to find out the improvement of the sample after the treatment using cartoon video. The data result of the test analyzed by using t-test. The findings of research show that cartoon video is effective to improve students’ listening skill. The score of pre-test is 51.6 and the mean score of post-test is 61.8 and the score of t-test is 3.98. It can be seen from t-observed is higher that t-table (3.98 > 2.064) at p = 0.5. the means Ha is accepted and Ho is rejected. Order than that, from the questionnaire data result cartoon video get the positive responses from the participant and can motivate the students in learning skill.